Bicycle Seat Designs and Their Effect on Seat and Handlebar Pressure in Male and Female Cyclists and Comfort and Stability in Experienced, Novice, Male and Female Cyclists on a Non-Stationary Bicycle - Bliss, Shantelle Gaye (Auckland University of Technology, 2005)
The bicycle is used as a means of transport, for recreation, or sporting activities and has undoubted fitness benefits. However, rider discomforts caused by seat contact, as well as various pathologies effect participation and enjoyment of this activity. The potential causes of these pathologies are discussed, along with the methods used, to establish the link between cycling and the various pathologies. Of particular interest in this thesis, is the measurement of the comfort and pressure of different seat designs. The level of comfort felt may be a precursor to pathological damage and be of prognostic value when assessing and designing seats. Pressure seems to be one of the best and most direct methods to assess the cyclist-seat interaction and offer information as to possible pathologies. The purpose of this thesis was to examine the effects that a standard, partial cut-out and complete cut-out seat have on comfort and stability, in male, female, novice and experienced cyclists, and seat and handlebar pressure in male and female cyclists on a non-stationary bicycle. With regards to the results, the standard seats’ mean and peak anterior seat pressures were significantly higher than the partial and complete cut-out seats (partial mean 19.1% and peak 16.8%; complete mean 66.1% and peak 72.6%). Mean and peak posterior pressure of the standard seat was significantly less than the cut-out seats (partial mean 16.5% and peak 12.3%; complete mean 21.6% and peak 21.2%). Overall peak pressure was significantly greater (22.8%) on the standard seat compared to the complete cut-out seat, but not significant (7.2%) compared to the partial cut-out seat design. Significantly lower mean handlebar pressure was associated with the standard (11.2%) and partial cut-out (14.7%) seat designs. There was no significant difference between seats for peak handlebar and mean overall pressure. The standard and partial cut-out seats had the highest sit bone, overall seat, overall riding, hand comfort and stability. The complete cut-out seat provided the greatest crotch comfort, but the lowest comfort and stability for all other factors investigated. It would seem that in terms of pressure distribution the partial cut-out seat would be the best option for cyclists, regardless of gender. In terms of comfort it is recommended that experienced and novice male cyclists should use the standard seat, experienced female cyclists use the partial cut-out seat and novice female cyclists could use either the standard or partial cut-out seat. However, pressure may be of more importance than comfort as it is more likely to influence pathological damage; therefore overall it is recommended that cyclists use the partial cut-out seat. The major draw back of the complete cut-out seat was the decreased perception of stability. With continued use of the complete cut-out seat this may become a better and more user-friendly option with a possible increase in perceived stability. Future research is required to examine any long-term effects in using cut-out seats in pathology prevention.
Keywords: Bicycles; Bicycle design; Bicycle construction; Bicycle performance